1996
DOI: 10.1271/bbb.60.366
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous Glycinebetaine Accumulation and Increased Salt-tolerance in Rice Seedlings

Abstract: Exposure of 28-day-old rice seedlings for 6 days to 150 mm NaCl was found to induce drastic decreases in relative water contents, chlorophyll, and proteins in the leaves. This effect was largely prevened when before the exposure to NaCl the seedlings were treated for 4 days with 15 mm glycinebetaine. Although rice plants do not accumulate glycinebetaine endogenously, added glycinebetaine was found to be taken up by the roots and to accumulate in the leaves to reach a concentration of up to 5.0 μmol per gram fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(54 citation statements)
references
References 0 publications
1
53
0
Order By: Relevance
“…Glycine betaine, a quaternary ammonium compound that occurs naturally in a wide range of plants, animals and microorganisms [33] is also a very effective compatible solute [34,35]. Although rice plants do not accumulate glycine betaine endogenously, Harinasut and co-workers [36] found that rice plants can uptake exogenous glycine betaine and accumulate it in leaves to help the plants to maintain quantum yield of PSII during salinity stress.…”
Section: Biosynthesis and Accumulation Of Organic Osmolytesmentioning
confidence: 99%
“…Glycine betaine, a quaternary ammonium compound that occurs naturally in a wide range of plants, animals and microorganisms [33] is also a very effective compatible solute [34,35]. Although rice plants do not accumulate glycine betaine endogenously, Harinasut and co-workers [36] found that rice plants can uptake exogenous glycine betaine and accumulate it in leaves to help the plants to maintain quantum yield of PSII during salinity stress.…”
Section: Biosynthesis and Accumulation Of Organic Osmolytesmentioning
confidence: 99%
“…BAD expression has previously been linked to salt tolerance in numerous plants (Ishitani et al 1995;Harinasut et al 1996;Wood et al 1996) and the gene expression of BAD2 (Fitzgerald et al Plant Mol Biol (2008) 68:439-449 445 2008) and the concentration of GABA (Kim et al 2007) has been found to increase in rice under salt stress. BAD2 has been shown to play a role in salt tolerance in rice, yet does not accumulate glycine betaine (Ishitani et al 1993;Rathinasabapathi et al 1993) and we have shown that GABald is the preferred substrate of BAD2.…”
Section: Does Fragrance Affect Plant Performance?mentioning
confidence: 99%
“…For example, 1) selective absorption of ions in roots (Badger and Ungar, 1990), 2) positive elimination of the absorbed salt (Matsushita and Matoh, 1991), and 3) storage of adaptation solutes in cytoplasm to maintain osmotic pressure (Munns and Termaat, 1986;Kalaji and Pietkiewicz, 1993). It has been proposed that rice acquires salt tolerance by excluding sodium ion from the roots (Akita and Cabuslay, 1990;Gregorio and Senadhira, 1993;Tsuchiya et al, 1994), and accumulation of proline and glycine betaine in leaves (Harinasut et al, 1996) for osmotic adjustment. However, these studies were made using cultivated rice species.…”
mentioning
confidence: 99%